Antigenic structure of the complete nonstructural (NS) 2 and 5 proteins of hepatitis C virus (HCV): anti-HCV NS2 and NS5 antibody reactivities in relation to HCV serotype, presence of HCV RNA, and acute HCV infection. - Zhang, Z X (1994)
Antigenic regions within the nonstructural (NS) 2 and 5 proteins of hepatitis C virus (HCV) were identified and characterized by the use of 127 overlapping synthetic peptides and a serum panel consisting of 167 human serum samples from persons with antibodies to HCV. Initially, 20 anti-HCV-positive serum samples were used to screen the peptides covering the complete NS2 and NS5 proteins. Among the 27 overlapping peptides spanning the NS2 protein of HCV, only the peptide covering residues 960 to 975 was recognized by human sera. Within the 100 peptides covering the NS5 protein, major linear antigenic regions were located at residues 2284 to 2329 within the putative NS5a and at residues 2584 to 2599 and 2944 to 2959 within the putative NS5b. Additional minor linear antigenic regions were also identified within the NS5. The sequence of the antigenic region of the NS2 protein is, unlike most parts of the NS2 protein, highly conserved among the described types of HCV, whereas the sequence of the major antigenic region of NS5 shows variability among HCV types. The recognition of a peptide corresponding to a part of the major region of NS5 was found to be dependent on HCV type. In 129 anti-HCV-positive serum samples, the prevalence of antibodies to the NS2 protein was found to be 23% among HCV RNA-positive sera and 10% among HCV RNA-negative sera. In the same samples, reactivity to the major linear antigenic regions of HCV NS5 was found in 68% of the HCV RNA-positive sera and 67% of the HCV RNA-negative sera. Of 18 serum samples from five patients with acute HCV infections, and who seroconverted with respect to anti-HCV, 4 were found to be reactive to one or more of the 100 NS5 peptides and in three serum samples the NS5 reactivities were found to shorten the time for serodiagnosis of cross-reactive with a region form residues 2584 to 2599 of NS5, which has 67% homology with a six-residue sequence of NS2. In conclusion, in this study we have identified and evaluated the potential use of synthetic peptides corresponding to linear antigenic regions of the NS2 and NS5 proteins.